Abnormal breathing pattern features in chronic refractory cough - Jordan Jeffery; Anne E. Vertigan; Sarah Bone; Peter G. Gibson (ERJ Open Research)
Background Chronic refractory cough (CRC) is a challenging condition that responds to speech pathology intervention. Clinical observation suggests abnormal breathing patterns occur in CRC and may be indirectly addressed as part of behavioural treatment, yet breathing pattern changes in CRC are poorly understood. The aims of this study were to 1) describe breathing patterns in patients with CRC, 2) compare breathing pattern features between patients with CRC and inducible laryngeal obstruction (ILO), and 3) estimate the effect of breathing pattern features on clinical measures of laryngeal sensory and motor dysfunction. Methods This retrospective cross-sectional observational study included 634 patients with CRC or ILO. A file audit of speech pathology assessment data was undertaken. Analysis of self-reported laryngeal symptoms (via questionnaires) and clinical assessment of voice and breathing of those with CRC and ILO was conducted. Results Most participants with CRC (73%) demonstrated at least one abnormal breathing pattern feature. The most common feature was thoracic breathing (69%) followed by oral breathing (33%). The type and prevalence of abnormal breathing patterns were similar between CRC and ILO. Abnormal breathing patterns were associated with reduced maximum phonation time (MPT); however, there was no association between these features and Newcastle Laryngeal Hypersensitivity Questionnaire scores. Conclusions Abnormal breathing features are common in patients with CRC and are not significantly different from those occurring in ILO. There is some association between abnormal breathing features and MPT, suggesting impairment of laryngeal motor function. Conversely, there is no association between abnormal breathing features and laryngeal hypersensitivity.